Penerapan Metode Experiential Learning Melalui Kegiatan Market Day untuk Menumbuhkan Jiwa Wirausaha Siswa di SMK PGRI 1 Salatiga - Sima Fatmawati; Muhammad Nuryanto; Agung Novianto Margarena (Jurnal Pengabdian kepada Masyarakat Radisi, 2025)
The low interest in entrepreneurship among vocational high school students is often caused by overly theoretical learning and a lack of real practical experience. This community service activity aims to foster an entrepreneurial spirit and improve the practical skills of grade X students at SMK PGRI 1 Salatiga through an intensive three-day training program. The implementation method uses an experiential learning approach consisting of three main stages: (1) internalization of the entrepreneurial mindset and introduction of the Business Model Canvas (BMC), (2) production preparation and marketing strategy, and (3) implementation through a buying and selling simulation (Market Day). Evaluation instruments used include pre-tests, post-tests, and direct observation during trading practices. The results of the activity show a significant increase in students' entrepreneurial literacy, as evidenced by an increase in the average score from 55 to 82. All student groups successfully produced product prototypes and conducted real transactions during the Market Day activity with sales success rates reaching the specified targets. Constraints found included limited production time and low initial student confidence, but these were overcome through intensive mentoring. The conclusion of this activity is that practical-based learning methods are effective in transforming students' mindsets from job seekers to opportunity creators.